PENGARUH UMUR DAN JUMLAH BENIH PER LUBANG TANAM TERHADAP HASIL PADI HITAM (Oryza sativa L) LOKAL SUBANG: Bahasa Indonesia - Karya; Putro Hairutomo Setiko; Joko Santoso (Program Studi Agroteknologi Faperta UNIBBA, 2023)
ABSTRACTThe aim of the study was to determine the appropriate age and number of seeds for the transfer process (Tapin) from the nursery to the planting area in order to obtain high growth and yield of black rice.This research was conducted in Lemah Duhur irrigated rice fields, Kiangroke Village, Banjaran District, Bandung Regency, West Java Province.This study used an experimental method with Split Plot Design using 2 factors, namely seed age (U) as the main plot consisting of 4 levels, namely u1 = 10 days after sowing, u2 = 15 days after sowing, u3 = 20 days after sowing scatter and u4 = 25 days after scatter. The number of seeds per planting hole (J) as child plots consisted of 4 levels, namely j1 = 1 seed per planting hole, j2 = 3 seeds per planting hole, j3 = 5 seeds per planting hole and j4 = 7 seeds per planting hole.Parameters observed were: number of tillers per clump, number of panicles per clump, weight of harvested dry unhulled (GKP) per clump, weight of dry harvested unhulled (GKP) per plot, weight of dry milled unhulled (GKG) per plot.The results showed that there was no interaction between the treatment of seed age and the number of seeds operted in the planting hole for all observation parameters. The highest average number of panicles per clump was found in u2j1, the highest average weight of harvested dry grain per clump was found in treatment u4j1, the highest average weight of harvested dry grain (GKP) per plot was found in treatment u4j1, the average the highest average weight of dry milled grain (GKG) per plot was in the u4j1 treatment. Key words : seed age, seed number, black rice, anthocyanin, aleurone